Impact of Diabetes Medication Therapy Adherence Clinic (DMTAC) appointment intervals on glycemic control in public health clinics across Perak, Malaysia - Ying Shan Beh; Keshamalini Gopalsamy; Sabrina Lai Fong Lee; V Paranthaman P. Vengadasalam (Malaysian Family Physician, 2022)
Introduction: Frequent diabetes medication therapy adherence clinic (DMTAC) appointments may lead to more rapid glycaemic control. This study aimed to evaluate the association between appointment intervals and glycaemic control (haemoglobin A1c [HbA1c] level) along with blood pressure (BP) and lipid profile (LP) during DMTAC appointments. Methods: This study retrospectively reviewed all recorded baseline and completed DMTAC data, including HbA1c level, LP and BP, of 318 eligible participants from 29 DMTACs across Perak. The participants were divided into shorter appointment interval (SAI) (≤30 days) and longer appointment interval (LAI) groups. Results: The majority of the baseline socio-demographic and clinical characteristics did not significantly differ between the SAI and LAI groups (p>0.05). Ischaemic heart disease (Odds ratio, OR=3.457; 95% CI=1.354–8.826; p=0.009) and hypertension (OR=0.521; 95% CI=0.276–0.992; p=0.044) were significantly associated with the appointment intervals. Upon completion of eight DMTAC visits, the HbA1c and FBS levels and DBP significantly improved (p<0.05). However, the mean HbA1c level (1.35±2.18% vs 0.87±2.11%, p=0.548), FBS level (1.25±4.82mmol/L vs 2.29±6.23mmol/L, p=0.538), SBP (3.28±21.82mmHg vs 3.65±18.35mmHg, p=0.343) and LDL level (0.09±0.98mmol/L vs 0.07±1.13mmol/L, p=0.246) did not significantly differ between the SAI and LAI groups. Conclusion: Longer DMTAC appointment intervals had similar improvement in glycaemic controls, blood pressure and lipid profiles as compared to shorter appointment intervals. A longer interval can be scheduled for lower-risk patients to optimise the use of human resources and minimise costs.